Cutting-edge green nanoclay nanocomposites—fundamentals and technological opportunities for packaging, dye removal, and biomedical sectors - Ayesha Kausar; Ishaq Ahmad; Osamah Aldaghri; Khalid H. Ibnaouf; M.H Eisa; Tran Dai Lam (Nanocomposites)
Nanoclays (layered silicates) have been applied as effective reinforcements for range of natural and synthetic polymeric matrices. Recent research has turned toward design and exploration of green nanocomposites using green polymers and nanoclay nanofillers. This state-of-the-art comprehensive overview debates design and performance prospects of green nanoclay nanocomposites. In this regard, numerous green polymers like poly(lactic acid), poly(vinyl alcohol), natural rubber, cellulose, starch, etc. have been considered. The effectiveness of green nanoclay nanocomposites has been analyzed through microscopic, electrical, mechanical, thermal, adsorption, and biomedical properties and wide span of applications such as packaging, dye removal, and biomedical sectors. Packaging based on cellulose/montmorillonite had very low water vapor transmission rate of 43 g/m2.day, whereas poly(lactic acid)/cellulose/montmorillonite packaging performed better with high water vapor transmission rate of 512–1861 g/m2.day. Poly(vinyl alcohol)/Cloisite Na possess optimum water vapor transmission rate of 533 g/m2.day. Nanocellulose/nanoclay packagings have also been found ideal due to low water vapor permeability (6.3–13.3 g.μm/m2.day.kPa) and oxygen permeability (0.07 cm3μm/m2.day.kPa) values. In dye removal applications, poly(ethylene glycol)/montmorillonite revealed optimum dye adsorption capacities of 190–237 mg/g, where chitosan/montmorillonite had high dye adsorption capacity of 446.43 mg/g. Poly(lactic acid)/modified Cloisite 20 A systems also own high dye adsorption efficiency of 97%. Poly(ɛ-caprolactone) and poly(vinyl alcohol) systems with montmorillonite nanoclay have effective drug delivery, tissue engineering, and wound healing applications. Furthermore, dielectric, mechanical, non-flammability, and self-extinguishing features of cellulose/montmorillonite nanocomposite systems have been reported. Future of these nanomaterials definitely relies on innovative design, facile fabrication strategies, and overcoming related challenges.